Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Hasil Belajar IPAS pada Siswa Kelas IV SD Inpres Bumi Sagu - Noni, Alfionita; Nuraini, Nuraini (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2022)
This study was conducted to address the low learning outcomes of students in Natural and Social Sciences (IPAS) subjects at SD Inpres Bumi Sagu, which is caused by the use of conventional teaching methods that make students passive and less motivated. To address this problem, this study implemented a cooperative learning model of the Teams Games Tournament (TGT) type that integrates collaboration, games, and healthy competition to increase student engagement and learning achievement. The purpose of this study was to determine the effect of the cooperative learning model of the TGT type on the learning outcomes of fourth-grade students at SD Inpres Bumi Sagu. This study used a quantitative approach with a Pre-Experimental One Group Pretest-Posttest Design. The subjects of the study were 24 fourth-grade students in one experimental class. Data were collected using multiple-choice tests that had been tested for validity and reliability. Data analysis was carried out using normality and linearity tests, followed by a Paired Sample T-Test with the help of SPSS 22 for Windows. The results showed that the average score of students increased from 46.87 (pretest) to 82.08 (posttest). The t-test results showed a significance value of 0.000 < 0.05, which confirmed the significant influence of the TGT model on students' science learning outcomes. Thus, the application of the TGT Type cooperative learning model has been proven effective in increasing student participation, motivation, and academic achievement in elementary school science learning.